Comparison of Physical and Mechanical Properties of Iranian and Foreign Composites: Comparison between Iranian and Foreign Composites - Valian, Azam; Golbari, Niusha; Nikaein, Mahsa (Journal of Dental School, 2025)
Objectives: Although dental composites offer clinical ease of use and a reasonable level of aesthetics, they still suffer from issues, such as low resistance to abrasion and fracture, post-polymerization shrinkage, and low stress tolerance, which restrict their applications. Given the current social conditions in the country and to support knowledge-based companies in the production of domestic composites, the present study aimed to investigate certain physical and mechanical properties of Iranian composites in comparison with foreign composites. Methods: Two types of commercially available foreign resin-based composites, Filtek Z250 (3M) and Den fil (Vericom), and the Iranian composite Trivers (Trimed) were investigated in terms of their mechanical and optical properties. For data analysis, ANOVA and post hoc tests at a 5% significance level were performed. Results: Z250 composite exhibited superiority in most mechanical properties, while Trimed composite exhibited lower mechanical properties, although these differences were not statistically significant for compressive strength(p=0.435). Conclusion: Based on the results of this study, Trimed composite showed promise for clinical application, although further laboratory and clinical investigations are required to improve the production quality of domestic composites.